Congenital Fibrosis of Extraocular Muscles - J Gordon Millichap (Pediatric Neurology Briefs, 1997)
The intracranial and orbital pathology and muscle pathology of chromosome 12-linked congenital fibrosis of the extraocular muscles are described in 3 affected members of a family in a report from Children’s Hospital, Harvard Medical School, Boston, and other centers.